Electronic bidding in the Contract of Public Works in the Palestinian Legislative Council - Mahmoud, Abdullah. D.; Darraj , Osama. I. (Dirasat: Shari’a and Law Sciences, 2020)
This study deals with the issue of electronic bidding in the government public works contract. The main problem of the study is in determining the legal nature of the subject of electronic bidding in the public works contract, and the extent to which it is subject to the general rules of administrative law. The researchers followed a descriptive approach in this study, by describing and analyzing the legal texts dealing with the subject of the study. The Palestinian legislator, in Decree-Law No. 8 of 2014 regarding public procurement, adopted electronic means in the procedures of electronic bidding, such as e-mail and the website, without explicitly referring to them. It also permitted relying on these means in some electronic bidding procedures, such as advertising, exchanging information, and submitting the bid, and gave the administrative authorities the power to organize them. However, when opening the bids and referring the bid, the legislator organized this stage in the traditional way where it stipulated that bids be opened in a public session and the presence of the bidders or their representatives, and refer the bid to the winning bidder in writing. The legislator did not adopt electronic means at this stage. The study concluded that the public works contract should be subject to the full jurisdiction of the administrative judiciary, with the need for the Palestinian administrative judiciary to become a cancellation and compensation judiciary so that it is concerned with all public works contract disputes, whether before or after the contract.